The effects of tetraethylammonium and cobalt ions on responses to extrinsic current in toad rods. - Fain, G L (1980)
1. Double-barrel micropipettes were used to pass pulses of current in darkness into single rods in the isolated, perfused retina of the toad, Bufo marinus. 2. In normal Ringer solution, current pulses evoked non-linear changes in membrane potential which varied as a function of current amplitude and of time. Responses to currents of both polarities showed slow relaxations toward the base line during the pulse, and the steady-state I-V curve exhibited a prominent outward rectification. 3. In Ringer containing 12 mM-TEA, the slow relaxation of voltage during outward current pulses was diminished, and the outward rectification was markedly reduced. In contrast Co2+, at a concentration in excess of that required to block Ca2+ spikes in rods, increased the receptor input resistance but did not reduce either the amplitude of the slow relaxation or the extent of outward rectification. 4. These experiments indicated that the outward rectification of rods is predominantly due to a conductance which is gated by voltage rather than by entry of Ca2+. 5. Long-lasting after-potentials followed the termination of outward current pulses. In normal Ringer the after-potentials were hyperpolarizing and were accompanied by an increase in input conductance. In TEA, the afterpotentials were depolarizing and were also accompanied by an increase in input conductance. The after-depolarizations in TEA were enhanced by Sr2+ and blocked by Co2+. These experiments suggest that the hyperpolarizing and depolarizing afterpotentials are produced by different mechanisms, the hyperpolarizing by an increase in K+ conductance, and the depolarizing by an increase in Ca2+ conductance.